Specific aspects of medical students’ mental health during the COVID-19 pandemic - Fedotova, Zoya (Psychosomatic Medicine and General Practice, 2021)
This is a conference abstract from the ІV Scientific and Practical Conference "Psychosomatic medicine: science and practice". It is dedicated to the specific aspects of medical students’ mental health during the COVID-19 pandemic.